Lean Production and Business Performance in Malaysian Manufacturing Industries - Rosman Iteng; Mohd Kamarul Irwan Abdul Rahim; Mohd Akhir Ahmad (International Journal of Supply Chain Management, 2017)
The primary purpose of this study is to empirically examine the relationships between lean production and business performance in Malaysian manufacturing industries. Grounded by the Socio-technical System Theory and the Program Theory, this study formulates and examines a conceptual model that links socially-oriented lean production, technically-oriented lean production, operational performance and business performance. This study utilizes two hundred and five manufacturing companies, selected randomly from the Federation of Malaysian Manufacturers Directory. The study measures senior production or lean managers perception of the lean production and the level of performances in their companies. This study applies structural equation modelling (SEM) method for data analysis using AMOS package. The result indicates that both socially-oriented lean production and technically-oriented lean production significantly contribute to the operational performance of the companies. The finding also suggests that operational performance partially mediates the relationship between lean production (both socially-oriented lean and technically-oriented lean) and business performance. The result also demonstrates a significant relationship between operational performance and business performance. This study presents empirical evidence in the field of management, particularly in the context of operations management. The findings would further enrich the existing knowledge in this field. Finally, this study would provide useful guidance for the managers to plan and maintain lean production in the organization as well as to generate new measures of lean production in order to enhance business performance at the company level.